Low levels of selenium in miscarriage - Güvenç, M; Güvenç, H; Karatas, F; Aygün, AD; Bektas, S (Wiley-Liss, 2002)
Few data are presented in the literature about selenium and miscarriage. The aim of this article was to study the relationship between the selenium status of pregnant women and miscarriage. A randomized, controlled trial was performed in Elazig State Hospital and Firat University Hospital. Serum and hair samples were obtained from 20 non-pregnant women, 32 healthy mothers with normal newborns, and 16 women who miscarried. Serum selenium levels, as ng/mL, and hair selenium levels, as ng/g, were determined on a Perkin-Elmer 1000 spectrophotometer by fluorometry. The mean serum and hair selenium concentrations of the women who miscarried (42.8 +/- 2.7 ng/mL, 276 +/- 6.6 ng/g, respectively) were significantly lower than those of the control healthy mothers (50.2 +/- 2.3 ng/mL. 300 +/- 6.1 ng/g, respectively) and the non-pregnant women (58.1 +/- 3.1 ng/mL, 315 +/- 7.6 ng/g, respectively). Maternal selenium deficiency during early gestation was thought to be one of the factors responsible in the pathogenesis of miscarriage. More studies on maternal selenium status during pregnancy are needed. J. Trace Elem. Med. 15:97-101. 2002. (C) 2002 Wiley-Liss, Inc.
Keywords: selenium; pregnancy; miscarriage